2018
DOI: 10.1257/mac.20150355
|View full text |Cite
|
Sign up to set email alerts
|

Firms and the Decline in Earnings Inequality in Brazil

Abstract: We document a large decrease in earnings inequality in Brazil between 1996 and 2012. Using administrative linked employer-employee data, we fit high-dimensional worker and firm fixed-effects models to understand the sources of this decrease. Firm effects account for 40 percent of the total decrease and worker effects for 29 percent. Changes in observable worker and firm characteristics contributed little to these trends. Instead, the decrease is primarily due to a compression of returns to these characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 37 publications
6
30
2
Order By: Relevance
“…As Alvarez et al (2018) pointed out, for a given level of earnings inequality, one extreme would be that the average earnings at all firms is the same but that inequality within firms mirrors exactly overall earnings inequality. The other is that all workers in each firm earn the same, in which case only differences in average earnings between firms drive earnings inequality.…”
Section: Earnings Inequality and Firmsmentioning
confidence: 99%
See 2 more Smart Citations
“…As Alvarez et al (2018) pointed out, for a given level of earnings inequality, one extreme would be that the average earnings at all firms is the same but that inequality within firms mirrors exactly overall earnings inequality. The other is that all workers in each firm earn the same, in which case only differences in average earnings between firms drive earnings inequality.…”
Section: Earnings Inequality and Firmsmentioning
confidence: 99%
“…There has not been much work on firms and earnings inequality in developing countries, mainly due to a lack of suitable data. One exception is Alvarez et al (2018), who examined the causes of declining earnings inequality in Brazil from 1996 to 2012 using matched firm and worker data. The authors showed that both the variance of log wages and the part explained by the difference between firms decreased during the period, but that it was an average of 66 per cent, much higher than the USA or EU countries in Lazear and Shaw (2009).…”
Section: Earnings Inequality and Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A striking feature of the steady rise in wage inequality that took place in the US from the 1970s onwards is that earnings increased more at higher percentiles of the earnings distribution, even for the same level of skill. The literature on this trend has grown considerably in recent decades, and has focused mainly on developed economies (the US and Western European countries) and some emerging economies (e.g., Brazil, China, see Alvarez, Benguria, Engbom, and Moser (2018); Appleton, Song, and Xia (2014); Messina and Silva (2017)). Only a few studies have dealt explicitly with recent developments in wage inequality in the CEE countries, which experienced a strong increase in wage dispersion during the transition to a market economy (Aristei & Perugini, 2014;Milanovic & Ersado, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 More recently, other authors have attributed much -even most -of the decline to the direct and indirect effects of a rising real minimum wage policy (Alvarez et al, 2016, and.…”
Section: Introductionmentioning
confidence: 99%